Pengembangan LKPD Fisika Berbasis STEM Untuk Meningkatkan Keterampilan Generik Sains Siswa Kelas XI SMA - Elija Pitri; Halimatus Sakdiah; Munzir Absa; Nuraini Fatmi; Muliani Muliani (Departement of Mathematics Education, 2024)
This research is a development research that aims: 1) to determine the feasibility of STEM-based physics LKPD on the developed temperature and heat material; 2) to know the improvement of students' generic science skills after using the developed STEM-based physics LKPD. The method used in this study is research and development (R &; D) with the ADDIE model. The subjects in this study were 20 students of grade XI Science 1, located in one of the schools in Bener Meriah. The data analysis techniques used to analyze each data are qualitative and quantitative values from the results of LKPD validation and student responses. The results of the research obtained are: 1) the percentage of feasibility of developing LKPD obtained from material expert validators is 87% with very feasible criteria, and the percentage obtained from media expert validators is 91% with very feasible criteria, and the percentage obtained from teacher expert validators is 96% with very feasible criteria; 2) the results of student responses in the usage trial obtained a percentage of 92% with very interesting criteria; 3) STEM-based physics LKPD is stated to improve students' generic science skills with an N-Gain value of 0.61 or 61% with the criterion